Development of an Integrated Inquiry Model the Value of Thought Economy of Mohammad Hatta in Social Studies Subject - Bangun Hutama Winata; Sunardi Sunardi; Djono Djono (BIRCU, 2020)
This study aims to develop inquiry models in social studies learning by integrating the values of Mohammad Hatta's democratic economic thinking in junior high schools in Lampung. The method used in this research is the development research (R&D) method. The subjects in this study consisted of material validators, model validators, and 48 junior high school students. The results of this development research show that the inquiry learning model integrated with the value of Mohammad Hatta's populist economic thought proved to be valid based on the assessment of the model expert and material expert. Based on the results of small group trials, limited trials and large group trials shows that the integrated inquiry learning model with the economic thought value of Mohammad Hatta proved to be effective and in accordance with needs analysis.